Implementation of pharmacogenetic interventions in clinical settings - Arranz, Maria (Henry Stewart Talks, 2025)
Pharmacogenetic (PGx) markers, Barriers to clinical implementation of PGx in psychiatry, PGx clinical benefits, PGx cost-effectiveness, PGx guidelines, PGx interventions